Transcriptome analysis of human peripheral blood mononuclear cells exposed to Lassa virus and to the attenuated Mopeia/Lassa reassortant 29 (ML29), a vaccine candidate. - Juan Carlos Zapata; Ricardo Carrion; Jean L Patterson; Oswald Crasta; Yan Zhang; Sachin Mani; Marti Jett; Bhawna Poonia; Mahmoud Djavani; David M White; Igor S Lukashevich; Maria S Salvato (Public Library of Science (PLoS), 2013)
Lassa virus (LASV) is the causative agent of Lassa Fever and is responsible for several hundred thousand infections and thousands of deaths annually in West Africa. LASV and the non-pathogenic Mopeia virus (MOPV) are both rodent-borne African arenaviruses. A live attenuated reassortant of MOPV and LASV, designated ML29, protects rodents and primates from LASV challenge and appears to be more attenuated than MOPV. To gain better insight into LASV-induced pathology and mechanism of attenuation we performed gene expression profiling in human peripheral blood mononuclear cells (PBMC) exposed to LASV and the vaccine candidate ML29. PBMC from healthy human subjects were exposed to either LASV or ML29. Although most PBMC are non-permissive for virus replication, they remain susceptible to signal transduction by virus particles. Total RNA was extracted and global gene expression was evaluated during the first 24 hours using high-density microarrays. Results were validated using RT-PCR, flow cytometry and ELISA. LASV and ML29 elicited differential expression of interferon-stimulated genes (ISG), as well as genes involved in apoptosis, NF-kB signaling and the coagulation pathways. These genes could eventually serve as biomarkers to predict disease outcomes. The remarkable differential expression of thrombomodulin, a key regulator of inflammation and coagulation, suggests its involvement with vascular abnormalities and mortality in Lassa fever disease.